Medulla oblongata and NCCs are central defenders against Streptococcus agalactiae infection of the tilapia brain - Hou, Xitan; Li, Qi (Frontiers in Immunology, 2024)
Various types of professional immune cells first emerge in fish and likely represent the primordial form and functions. Recent advancements revealed the direct connection between the central nervous system and the immune system in the mammalian brain. However, the specifics of brain-immune networks in the fish and the underlying mechanisms of teleost's brain against pathogen infection have not been fully elucidated. In this study, we investigated the distribution of markers representing cerebral cells associated with protection and professional lymphocytes in the seven major components of the Nile tilapia brain through RNA-Seq assay and observed the most dominant abundance in the medulla oblongata. The subsequent challenge test revealed the non-specific cytotoxic cells (NCCs) exhibited the strongest response against streptococcal infection of the brain. The presence of NCCs in the brain was then confirmed using immunofluorescence and the cytotoxic effects usually induced by NCCs under infection were determined as well. Collectively, these findings contribute significantly to comprehending the mechanism of fish neuroimmune interaction and enhancing our understanding of its evolutionary development.